Clinical case of treatment of a patient with pulmonary embolism after microsurgical excision of arteriovenous malformation of the right parietal lobe - A. G. Pronin; N. Y. Sivokhina; M. A. Maslennikov; V. V. Artsishevskay; A. S. Salov; A. R. Rakhmatullina; D. K. Glukhov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
The article presents a clinical observation of successful treatment of a patient with intrahospital hemodynamically significant pulmonary embolism, which frolicked in the first 35 hours after bone-plastic trepanation in the right temporal-parietal region for the purpose of microsurgical excision of arteriovenous malformation of the right parietal lobe.